2007
DOI: 10.1007/s00213-007-0769-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Schild regression analyses using nonselective 5-HT2C receptor antagonists in a rat operant behavioral assay

Abstract: Taken together, these antagonism profiles suggest that the agonists MK212 and mCPP produce their rate-decreasing effects through a combination of 5-HT receptors with the 5-HT(2C) receptor playing a prominent but not exclusive role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…have been widely used in vivo to support the participation of 5-HT 2B in several animal models of disease 73,74,86,87,[89][90][91][124][125][126] , our results suggests the possibility that AhR might have influenced some of these previous results and might have even contributed to the pathological effects of deregulated 5-HT 2B expression or function. As an example, since AhR mediates IL-10 production and promotes immunological tolerance after macrophage capture of apoptotic cells 127 , AhR might contribute to the anti-inflammatory effect of 5-HT 2B in mouse microglia 71 and human monocytes 72 .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…have been widely used in vivo to support the participation of 5-HT 2B in several animal models of disease 73,74,86,87,[89][90][91][124][125][126] , our results suggests the possibility that AhR might have influenced some of these previous results and might have even contributed to the pathological effects of deregulated 5-HT 2B expression or function. As an example, since AhR mediates IL-10 production and promotes immunological tolerance after macrophage capture of apoptotic cells 127 , AhR might contribute to the anti-inflammatory effect of 5-HT 2B in mouse microglia 71 and human monocytes 72 .…”
Section: Discussionmentioning
confidence: 65%
“…Since human anti-inflammatory M-MØ express 5-HT 7 and 5-HT 2B serotonin receptors 40 and clinically relevant drugs (anesthetics, SSRIs, antimigraine drugs) act via 5-HT 2B 49,51-54 , we sought to determine the consequences of 5-HT 2B engagement in human macrophages using BW723C86, an 5-HT 2B agonist with 10-fold and 100-fold selectivity over human 5-HT 2C and 5-HT 2A , respectively 85 , amply used as in vivo 54,73,74,[86][87][88][89][90][91] and ex vivo 28,66,70 , and with potential therapeutic effects 73,74,91 . Transcriptional profiling of BW723C86-treated M-MØ ( Figure 1A) revealed that the agonist increased the expression of 357 annotated genes and downregulated the expression of 398 genes (adj p<0.002) ( Figure 1B, Supplementary Tables II and III).…”
Section: The Bw723c86 Agonist Modulates the Transcriptional Signaturementioning
confidence: 99%
See 1 more Smart Citation
“…(C) ERK-1/2 phosphorylation in mHypoA-2/10 cells was measured by whole-cell ELISA after stimulation with increasing concentration of 5-HT or WAY-161,503 for 3 minutes. Data of four experiments performed in quadruplicate were interacts with other CRE-activating 5-HTRs besides HT 2C R. To further evaluate the role of distinct 5-HTR in hypothalamic CRE activation, we took advantage of the 5-HT 2C R antagonists SB-242,084 or RS-102,221, the 5-HT 2A R antagonist EMD-281,014, and the 5-HT 2B R antagonist RS-127,455 (Cussac et al, 2000;Walker et al, 2007). Both 5-HT 2C R, but none of the other antagonists, blunted WAY-161,503-induced CRE-dependent gene expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…agonist with 10-fold and 100-fold selectivity over human 5-HT2C and 5-HT2A, respectively 86 , amply used as in vivo 54,73,74,[87][88][89][90][91][92] and ex vivo 28,66,70 , and with potential therapeutic effects 73,74,92 .…”
Section: The Bw723c86 Agonist Modulates the Transcriptional Signaturementioning
confidence: 99%